2019
DOI: 10.1111/and.13316
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of DNA fragmentation in human spermatozoa: Are sperm chromatin structure analysis and sperm chromatin dispersion tests (SCD‐HaloSpermG2 ® ) comparable?

Abstract: Men affected with idiopathic infertility often display basic spermiogramme values similar to fertile individuals, questioning the diagnostic impact of the World Health Organization (WHO) thresholds used. This study explored sperm DNA fragmentation in single ejaculates from 14 fertile donors and 42 patients with idiopathic infertility providing semen for assisted reproductive techniques in a university fertility clinic. Each ejaculate was simultaneously studied for sperm DNA fragmentation by the flow cytometer‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
1
7
0
1
Order By: Relevance
“…It is currently challenging for researchers and clinicians to compare DFI derived from different assays across diverse studies to assess the risk of male factor infertility. In our results, a higher DFI was recorded when using a SCD kit than when using SCSA, and a similar result has been found in other studies [20,24,25]. The results regarding CV and technical repeatability appear to be contentious; the Halosperm pioneer laboratory reported a CV of 6%-12% [10], which is much lower than our observed values (2%-54% for CANfrag and 7%-62% for Halosperm).…”
Section: Discussionsupporting
confidence: 89%
“…It is currently challenging for researchers and clinicians to compare DFI derived from different assays across diverse studies to assess the risk of male factor infertility. In our results, a higher DFI was recorded when using a SCD kit than when using SCSA, and a similar result has been found in other studies [20,24,25]. The results regarding CV and technical repeatability appear to be contentious; the Halosperm pioneer laboratory reported a CV of 6%-12% [10], which is much lower than our observed values (2%-54% for CANfrag and 7%-62% for Halosperm).…”
Section: Discussionsupporting
confidence: 89%
“…For these reasons, various authors have recommended the introduction of sperm DNA fragmentation analysis as a routine and complementary test in semen analysis (Lewis & Aitken, 2005;Fortunato et al, 2013). In this study, we uses the SCD test due its high sensitivity to detect sperm with DNA fragmentation (Chohan et al, 2006;Zhang et al, 2010;Liffner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(Fernandez et al, 2003;Fernandez et al, 2005). Studies have shown that SCD has high sensitivity to detect sperm with DNA fragmentation (Chohan et al, 2006;Zhang et al, 2010;Liffner et al, 2019). Different studies using SCD test have determined the reproductive capacity of the sperm and its correlation with seminal parameters and embryo quality after in vitro fertilization (Velez de La Calle et al, 2008;Feijó & Esteves, 2013;Tandara et al, 2013;Acosta & Dueñas, 2014;Acosta et al, 2015;Borges et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA integrity is a critical parameter that plays a fundamental role in embryo development and pregnancy rate (Liffner et al., 2019). Both sperm chromatin structure assay (SCSA) and the terminal deoxynucleotidyl transferase‐mediated deoxyuridine triphosphate nick end labelling (TUNEL) assay are gold standard for identification of the sperm DNA damage.…”
Section: Discussionmentioning
confidence: 99%